(untitled) (International Journal of Environmental Sciences, 2025)
Theme parks have become prominent as important recreational areas for both social interaction and economic development in modern city life. Theme parks, which offer leisure, recreation and cultural experiences, increase the attractiveness of cities and provide a contribution to the local economy. Within this scope, the study examines theme parks by taking Ankapark as an example. In the study, a qualitative research method has been applied and both semi-structured interviews have been conducted with 17 people who have previously visited Ankapark and online user reviews obtained from Google Reviews and Tripadvisor have been analyzed. The data collected within the scope of the research have been analyzed using Excel, NVivo and MAXQDA programs; analysis methods such as code matrix browser, code trends matrix and word cloud have been used. The results of the analysis revealed that Ankapark failed to achieve its social and economic goals due to deficiencies in the design and operation processes. The respondents' opinions pointed to price policies, infrastructure deficiencies and sustainability problems. This study, which emphasizes the critical importance of planning and stakeholder participation in theme park projects, also offers suggestions for future projects.